Wandering Dreams and Social Marches: Varieties of Paganism in Late Victorian and Edwardian England - Hallett , Jennifer (Pomegranate, 2007)
This article takes paganism to mean the use of images and ideas from the ancient pre-Christian Mediterranean world. It explores two varieties of paganism in operation in England during the closing decades of the nineteenth century and the first decade of the twentieth: one based in literature, the other based in intellectual debates and early socialism. While the former has previously been discussed by scholars, the addition of the latter adds a new dimension to the examination of paganism during this period. These two varieties of paganism, in their own ways, negotiated versions of paganism specifically designed to cater for the spiritual and human aspirations of the radical Victorians and Edwardians who imagined them.